Aluminum coating by fluidized bed chemical vapor deposition on austenitic stainless steels AISI 304 and AISI 316 (2015)
Aluminum coatings were deposited on stainless steels AISI 304 and AISI 316 at a temperature range from 560 to 600°C by CVD-FBR, using a bed consisting of a 10% aluminum powder and 90% of bed inert (alumina) which was fluidized with Ar and an activator mixture of hydrochloric acid with hydrogen (HCl/H2). The coating without heat treatment includes the follow species: Al13Fe4, Fe2Al5, FeAl2 and Al5FeNi for both steels. In addition, the heat treatment causes the aluminum to diffuse into the substrate and the iron diffuse towards the surface of the coating, making the transformation of previous existing compounds to FeAl, Fe2Al5, FeAl2, Al0.99Fe0.99Ni0.02, AlNi and Fe2AlCr. Thermodynamic simulation was conducted with the Thermo-Calc software to obtain information of the possible composition and amount of deposited material, for selected conditions. The specimens coated and uncoated were exposed at 750 ºC in an atmosphere where the vapor was transported to the samples using a N2 flow of 40 ml/min plus 100% water vapor (H2O). The two uncoated substrates behaved differently, since the steel AISI 304 performed well and gained little weight (0.49 mg/cm2), compared to the steel AISI 316 that lost too much weight (25.4 mg/cm2). Coated steels gained little weight during thousand hours of exposure (0.26 mg/cm2) and support very well the corrosive attack compared to uncoated substrates.